Advances in mathematics - Busemann, Herbert, 1905- (New York : Academic Press, 1965)
Vols. 1 and 2 are collected vols. of separately published fascicles issued 1961-1968.
Includes bibliographies.
Editor: 1965- H. Busemann.
Annual, v. 2-3; 1968-69
Keywords: Mathematics